Dual Doping: An Effective Method to Enhance the Electrochemical Properties of Li10GeP2S12‐Based Solid Electrolytes. Issue 12 (13th August 2015) - Yang, Kun; Dong, Jianying; Zhang, Long; Li, Yueming; Wang, Limin
Abstract : Multiple doping is widely used to improve the performance of a material, including its electrical transport, mechanical, and photovoltaic properties. In this paper, Sn–Se dual‐doped Li10 GeP2 S12 (LGPS, thio‐LISICON II analogue) electrolytes were synthesized via ball milling and sintering and compared with those Sn or Se single‐doped. Successful Sn and/or Se substitution expanded the unit cell and formed SnSe 4 4 − units, which were verified by X‐ray powder diffraction, energy‐dispersive X‐ray spectroscopy, and Raman spectroscopy. In contrast to the limited benefits of Se single doping and the negative effects of Sn single doping, Sn–Se dual doping demonstrated up to 53% enhancement in ionic conductivity. More importantly, Sn–Se dual‐doped LGPS showed an extremely low activation energy of 16 kJ/mol, which is one of the lowest known values for lithium ion conductors; as well as one of the widest electrochemical windows of 8 V. Sn–Se dual‐doped LGPS is a promising electrolyte for advanced all‐solid‐state batteries.